(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
This paper examines the critical dynamic between good governance and sustainable development, emphasizing their shared cornerstones in institutional probity, responsibility, and enduring societal welfare. Leveraging global governance frameworks and the sustainable development goals (SDGs), this delineates the role of transparency, inclusive participation, robust regulation, and rule of law in shaping development outcomes across economic, social, environmental, and institutional spheres. The analysis accentuates deep-rooted governance issues like corruption, administrative inefficiencies, policy gap, and technological variations—that restrict sustainability efforts, particularly in developing and transition economies. Through discerning international instances, the study illustrates how governance innovations, information systems, and inclusive institutions heighten the prospects of just and adaptable progress. The research wraps up by determining the fundamental action items for building institutional resilience, mainstreaming shared input, and embracing climate-resilient management approaches. The paper thereby strengthens the argument that sustainable development’s success is deeply tied to the standard of responsiveness and credibility of governance systems.